Contribuição ao estudo fitoquímico da espécie justicia gendarussa burm f. e síntese de derivados da biflorina com potenciais atividades biológicas - Souza, Luciana Gregório da Silva (2016)
This work is divided in two parts. The first part, shown the phytochemical study of the species Justicia gendarussa Burm. F. The ethanolic extract from the leaves of J. gendarussa was subjected to chromatographic fractionations, leading to the isolation of seven constituents: the triterpenes, squalene (JGFC1) and lupeol (JGF-C4), the mixture of sterols, sitosterol and stigmasterol (JGF-C2), a fatty acid ester (JGF-C3), and five novel alkaloids which were named Brazoide A (JGF-1), Brazoide B (JGF-4), Brazoide D (JGF-5) and Brazoide E (JGF-3). The second part of the work deals with obtaining derivatives of biflorin, in which two hydrazones (B-1 and B-2), three oximes (B- 3, B-4 and B-5), and a phenazine (B-6). Chromatographic methods including High Performance Liquid Chromatography (HPLC) were used for the purification of the substances. The structural determination was performed using spectrometric techniques such as infrared spectroscopy (IR), Mass Spectrometry (EMAR-IES) and hydrogen Nuclear Magnetic Resonance (1H NMR) and carbon-13 (13C NMR), including Two-dimensional techniques (COSY, HSQC and HMBC) and comparison with data recorded in the literature. The B-1, B-2, B-3, B-4, B-5 and B-6 derivatives were tested against the cell growth of three human tumor cell lines (SF-295 - glioblastoma, OVCAR - Breast, HCT-116 - colon), showing no significant activity against any tested lineage. Antibacterial activity tests against Enterococcus faecalis (ATCC 4083), Staphylococcus aureus (ATCC 25923), Staphylococcus aureus (358), Escherichia coli (ATCC 10536), Proteus vulgaris (ATCC 13315) and Escherichia coli (27) of which all showed activity against at least two bacterial strains. Oximes showed the best results against all strains tested, with antibacterial potential even higher than the antibiotics used as a positive standard.